BMD-Related Genetic Risk Scores Predict Site-Specific Fractures as Well as Trabecular and Cortical Bone Microstructure - Nethander, Maria (J Clin Endocrinol Metab, 2020)
CONTEXT: It is important to identify patients at highest risk of fractures. OBJECTIVE: To compare the separate and combined performances of bone-related genetic risk scores (GRSs) for prediction of forearm, hip and vertebral fractures separately, as well as of trabecular and cortical bone microstructure parameters separately. DESIGN, SETTING, AND PARTICIPANTS: Using 1103 single nucleotide polymorphisms (SNPs) independently associated with estimated bone mineral density of the heel (eBMD), we developed a weighted GRS for eBMD and determined its contribution to fracture prediction beyond 2 previously developed GRSs for femur neck BMD (49 SNPs) and lumbar spine BMD (48 SNPs). Associations between these GRSs and forearm (n(cases) = 1020; n(controls) = 2838), hip (n(cases) = 1123; n(controls) = 2630) and vertebral (n(cases) = 288; n(controls) = 1187) fractures were evaluated in 3 Swedish cohorts. Associations between the GRSs and trabecular and cortical bone microstructure parameters (n = 426) were evaluated in the MrOS Sweden cohort. RESULTS: We found that eBMD(GRS) was the only significant independent predictor of forearm and vertebral fractures while both FN-BMD(GRS) and eBMD(GRS) were significant independent predictors of hip fractures. The eBMD(GRS) was the major GRS contributing to prediction of trabecular bone microstructure parameters while both FN-BMD(GRS) and eBMD(GRS) contributed information for prediction of cortical bone microstructure parameters. CONCLUSIONS: The eBMD(GRS) independently predicts forearm and vertebral fractures while both FN-BMD(GRS) and eBMD(GRS) contribute independent information for prediction of hip fractures. We propose that eBMD(GRS) captures unique information about trabecular bone microstructure useful for prediction of forearm and vertebral fractures. These findings may facilitate personalized medicine to predict site-specific fractures as well as cortical and trabecular bone microstructure separately.